An Analysis of Regional Economic Advantage and Specialization (Shift-Share Esteban Marquillas Model Approach) and Analysis of Its Accessibility in Banyumas Regency - Rian Destiningsih; Andhatu Achsa (EKO-REGIONAL, 2018)
This study aimed (1) to identify the competitive advantage, specialization and effect of sectors allocation in Banyumas Regency in 2010-2015; (2) to identify region with the most advantageous position in terms of accessibility level. The result indicated that (1) competitive and specialized sectors in Banyumas Regency were mining and excavation sector, procurement of electricity and gas sector, construction sector, big scale trade and retail, car and motorcycle repair, transportation and warehousing sector, provision of accomodation and food and beverage sector, information and communication sector, financial and insurance services sector, real estate sector, corporate service sector, government administration sector, defense and compulsory social security, education service sector, health service and social activities sector, and other service sectors. (2) In terms of accessibility, Banyumas Regency had the second advantageous position after Purbalingga Regency when compared to regencies in Karesidenan Barlingmascakeb. Based on the accessibility of each sub-district in Banyumas Regency, the sub-district with the most advantageous position to interact with the sub-districts in Banyumas Regency was Tambak sub-district. This can be seen from the lowest CQ value of Tambak sub-district.Keywords: Shift-Share Esteban Marquillas, Accessibility, Connectivity Quotient.